How to Imagine a New Community from Science Fiction: A Pedagogical Dramaturgy of Silence, for a Slow Education - Andrés González Novoa; Pedro Perera Méndez (MDPI AG, 2023)
Europe has just established the first regulation for artificial intelligences. Large technology corporations and private educational institutions are already imagining neural networks educating us. Has anyone stopped to think about who, how and for what purpose we humans are going to educate machines? The Spanish critical pedagogy research team (PEDACRI), after participating in international conferences on digital education, robotics, ethics in the metaverse and cartography of hyperreality and participating in various publications on the challenges of pedagogy and ethics in the technologisation of educational processes, reflects in this essay on the challenges and questions we need to ask ourselves to imagine the post-human or trans-human community to come. Reviewing works coming from philosophy and those plays, series and films that address the future and the relationship between humans and machines, we analyse the opportunities and threats that can humanise machines or programme them as soulless weapons, which can civilise us or return us to a state of barbarism. The word robot, let us not forget, is derived from the Polish word roboca, which means "slave". Will we be able, as the replicant in Blade Runner wonders, to programme silence? What can philosophy and pedagogy contribute to the ethical programming of algorithms?